1998
DOI: 10.1385/jmn:11:2:165
|View full text |Cite
|
Sign up to set email alerts
|

The Role of NeuroD as a Differentiation Factor in the Mammalian Retina

Abstract: NeuroD, a vertebrate homolog of Drosophila atonal gene, plays an important role in the differentiation of neuronal precursors (Lee et al., 1995). We have investigated whether NeuroD subserves a similar function in mammalian retinal neurogenesis. Expression of NeuroD is detected in successive stages of retinal neurogenesis and is associated with a differentiating population of retinal cells. The association of NeuroD predominantly with postmitotic precursors in early as well as late neurogenesis suggests that N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 56 publications
1
33
0
Order By: Relevance
“…Although previous studies of NeuroD1 in the retina have shown that the gene is expressed in developing and mature photoreceptors (Kanekar et al, 1997;Ahmad et al, 1998;Wang, 1998, 2004;Morrow et al, 1999), double-labeling for NeuroD1 expression and BrdU shows that the majority of the NeuroD1-expressing cells are postmitotic. This is consistent with our previous findings that TR␤2 and its heterodimeric partner, RXR␥, are also expressed in newly postmitotic cone photoreceptors (Ng et al, 2001;Roberts et al, 2005Roberts et al, , 2006Jones et al, 2007).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Although previous studies of NeuroD1 in the retina have shown that the gene is expressed in developing and mature photoreceptors (Kanekar et al, 1997;Ahmad et al, 1998;Wang, 1998, 2004;Morrow et al, 1999), double-labeling for NeuroD1 expression and BrdU shows that the majority of the NeuroD1-expressing cells are postmitotic. This is consistent with our previous findings that TR␤2 and its heterodimeric partner, RXR␥, are also expressed in newly postmitotic cone photoreceptors (Ng et al, 2001;Roberts et al, 2005Roberts et al, , 2006Jones et al, 2007).…”
Section: Discussionmentioning
confidence: 94%
“…NeuroD1 is expressed in the developing and mature retina in both photoreceptors and amacrine cells in frog, chick, and mammals (Kanekar et al, 1997;Ahmad et al, 1998;Yan and Wang, 1998;Morrow et al, 1999;Pennesi et al, 2003). In other regions of the CNS, although primarily expressed in postmitotic cells, NeuroD1 has also been found in some mitotically active progenitor cells (Lee et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrophysiological recordings allowed a single-cell analysis in the densely packed hilar region, and we obtained direct evidence for the presence of normal interneurons but a virtual lack of differentiated GC. Because both cell types are derived from one pool of early progenitors, it is possible that neuronal bHLH proteins participate also in a late step of lineage decision (Ahmad et al, 1998;Yan and Wang, 1998;Morrow et al, 1999). However, the abundance of immature cells that express some (but not all) neuronal differentiation markers demonstrates that one essential function of NEX, BETA2/NeuroD, and presumably also NDRF, is the control of terminal neuronal differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested a role in differentiation, whereas initial gain-of-function experiments (involving overexpression in frog oocytes) demonstrated, by neurogenic conversion, that at least BETA2/NeuroD and NDRF/NeuroD2 can act as determination factors (Lee et al, 1995;McCormick et al, 1996). Given the uncertainty of abnormal timing in these and related experiments involving ectopic expression (Ahmad et al, 1998;Yan and Wang, 1998;Morrow et al, 1999), the normal function of neuronal bHLH proteins has remained unclear. Moreover, initial gene targeting experiments have revealed that BETA2/NeuroD is essential for pancreas development, and its loss of function is lethal, presumably because of early postnatal diabetic failure (Naya et al, 1997).…”
Section: Abstract: Dentate Gyrus; Granule Cells; Neuronal Differentimentioning
confidence: 99%